Compressive mechanical behavior and model of composite elastic-porous metal materials. (17th December 2021) - Yang, Pei; Zhou, Tao; Jia, Di; Qin, Zhiqiang; Wu, Yiwan; Bai, Hongbai
Abstract: This work presents the experimental characterization and theoretical modeling of composite elastic-porous metal materials (C-EPMM). C-EPMM is a novel porous metallic damping material made of wire mesh and wire helix. A series of quasi-static compressive experiments were carried out to investigate the stiffness and energy absorption ability of the C-EPMM with different mass ratios. The experimental results show that the mass ratios can significantly affect the stiffness and loss factor of C-EPMM. To efficiently predict the nonlinear mechanical properties of the C-EPMM a theoretical model of C-EPMM was proposed for the first time, the model was based on the manufacturing process. A comparison between the predicted data and the experimental data was conducted. The results show that the theoretical model can accurately predict the mechanical performance of C-EPMM. The conclusions derived from this work can provide a new method for adjusting the mechanical performance of EPMM in applications.